Effects of transcutaneous electrical nerve stimulation on maximal voluntary contraction in women with temporomandibular dysfunction: randomized clinical trial - Guilherme Lemos Monteiro dos Santos; Fabiane Miron Stefani (BrJP, 2024)
BACKGROUND AND OBJECTIVES: The purpose of this study was to evaluate the effectiveness of Transcutaneous Electrical Nerve Stimulation (TENS) combined with manual therapy in women diagnosed with muscular Temporomandibular Dysfunction (TMD) with or without Reduced Disc Displacement (RDD). The objective was to evaluate the action of manual therapy in conjunction with TENS as a therapeutic tool for treating TMD, analyzing the electromyographic tasks in MVC and in rest, and measuring pain scores with the Visual Analog Scale (VAS). METHODS: This study has a blinded randomized clinical trial design. In this context, after screening, 11 women with a diagnosis of muscular TMD with or without RDD, aged between 18 and 39 years, were investigated. The 11 women were randomly divided into two intervention groups, one receiving manual therapy alone and the other receiving manual therapy together with TENS. The participants were assessed using the Diagnostic Criteria for Temporomandibular Disorders (DC/TMD) and MBGR protocols for inclusion and exclusion, using the VAS to analyze pain, and Surface Electromyography (EMG) to analyze MVC and rest muscle activation. RESULTS: Lower MVC and rest values were observed after the intervention in both intervention groups. Manual therapy alone was as effective as manual therapy combined with TENS. There was no difference between the manual therapy group (MG) and manual therapy+TENS group (TG) in the VAS scores, however when comparing pre- and post-intervention, lower values were observed in the scores of both groups. CONCLUSION: Both groups showed a reduction in pain, but the combination of TENS and manual therapy showed a slight improvement in the stability of the masticatory muscles compared to manual therapy alone. With or without TENS, muscle relaxation and analgesia were achieved.